"AND GRAVES GIVE UP THEIR DEAD": THE OLD CURIOSITY SHOP, VICTORIAN PSYCHOLOGY, AND THE NATURE OF THE FUTURE LIFE. Issue 2 (10th March 2014) - Stolte, Tyson
<x content-type="archive" xml:space="preserve">Abstract</x> Midway through the old curiosity shop (1840–41), Quilp returns home to discover his own wake in progress upstairs. He has been absent for three days, dogging the footsteps of the friends and family searching for Nell: materializing at Little Bethel, the chapel Kit's mother attends, or rising from the larder of the inn to which the single gentleman and Kit's mother retire after discovering from Mrs. Jarley that they have just missed Nell. Quilp's wife, having heard nothing from him all this time, has concluded that he has drowned, and so Quilp finds her, her mother, and the lawyer Sampson Brass at work on a descriptive advertisement for his corpse. As Quilp looks on, the group insultingly anatomizes him – "Large head, short body, legs crooked" (Dickens 382; ch. 49) – a process punctuated by the slightly inebriated Brass's musings on the afterlife to which the dwarf might have flown. Brass considers the possibility that the recently deceased might be at that moment watching from the next world, and this thought leads to another platitude about the dead: <disp-quote> "I can almost fancy" said the lawyer shaking his head, "that I see his eye glistening down at the very bottom of my liquor. When shall we look upon his like again? Never, never! One minute we are here" – holding his tumbler before his eyes – "the next we are there" – gulping down its contents, and striking himself emphatically a little below the chest – "in the silent tomb." (381; ch. 49) </disp-quote> Brass's sentiments are, at least for a moment, tantalizingly vague. We, of course, know precisely where Quilp is – behind the door – but Dickens's suspension of Brass's speech until the lawyer has finished his drink seems to offer a much less definite possibility: that once the dead are no longer "here, " they are simply "there." But where, when it comes to the future life, is that? Only in the silent tomb? For all its lack of seriousness, this scene gets to the heart of a fundamental curiosity in this novel about what might await us in the next life. In other words, while readers of the novel have tended to focus most intently on whether Little Nell might die, the novel itself seems equally interested in what might happen to Nell – and to us – after death.